Common Indications of Exchange Transfusion in Neonates with Jaundice Presenting to a Tertiary Care Health Facility - Muhammad Ashfaq, Bader-U-Nisa, Shabeeta Bai, Quratulain Sial, Syed Habib Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of common indications of exchange transfusion in neonates with jaundice presenting to a tertiary care health facility. Study Design: A descriptive cross-sectional study. Place and Duration: Department of Paediatrics, National Institute of Child Health, Karachi Pakistan, from January 2022 to June 2022. Methodology: All neonates up to 28 days of either gender presenting with jaundice were included. Details about gender, ethnicity, blood group, feeding practices and indications of exchange transfusion were noted. Results: The mean age of the patients was 10.71±9.68 days. There were 66 (50.4%) males and 65 (49.6%) females. The Mean weight and gestational age were found to be 3.39±0.37 kg and 39.34±1.07 weeks respectively. Feeding practice among majority (n=78, 59.5%) of the mother was mixed (n=78, 59.5%). ABO incompatibility was observed in 31 (23.7%), Rh incompatibility in 24 (18.3%) and unidentified cause in 11 (8.4%) neonates. Practical Implications: For hyperbilirubinemia in neonates, ABO incompatibility was found to be the most frequent causative factor behind exchange transfusion. Conclusion: ABO incompatibility was found to be the most common indications of exchange transfusion followed by Rh incompatibility in neonates with jaundice presenting to tertiary care facility. Keywords: ABO incompatibility, exchange transfusion, jaundice, Rh incompatibility, neonates.